PEMODELAN REGRESI BERGANDA UNTUK FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK IMPLORA MENGGUNAKAN PLATFORM TIKTOK SHOP DI PURWAKARTA - Farida Apriani (RAGAM: Journal of Statistics & Its Application, 2025)
The cosmetics industry in Indonesia is experiencing rapid growth and has managed to dominate the domestic market, so many cosmetic brands continue to innovate, including the Implora brand. Implora is a cosmetic that can be reached by all strategists looking to be known, namely promotions that use the tiktok shop application. Tiktok shop presents an innovative "Shoppertainment" concept by combining the uniqueness of the TikTok platform, especially entertaining and engaging content, with direct shopping features. This study aims to find out and conduct modelling to determine the influence of social media marketing, product quality, and consumer trust on the purchase of Implora cosmetic products on the TikTok Shop. This study uses primary data in the form of a questionnaire with sampling techniques, namely random and purposive sampling. The respondents are 191 students university in Purwakarta. The method used was descriptive analysis and multiple linear regression; the model obtained using α=0.05, namely  Y=-1.154+0.077X1+0.399X2+0.725X3 with a determination coefficient value of 85.8%. The dominance of the age who buy this product is 19-24 years old and the variables that have a significant influence from this study are product quality and consumer trust, but the social media marketing variables are still maintained, the existence of these findings can provide a more focused strategy direction for implora products to strengthen product quality and build trust while still utilizing social media such as tiktokshop to expand wide marketingT